Caracterización de las propiedades del aire húmedo (Sicrometría) del microclima de la hacienda Vegas de la Clara (nordeste antioqueño, Colombia) (2007)
ABSTRACT: An exploratory descriptive statistical analysis was applied for determining the characteristics of the humid air (Sicrometría) of the microclimate of Vegas de la Clara farm (northeast antioqueño) were determined, for which the atmospheric pressure (910.41 kg/cm2), ambient temperature (25 ± 3.264 °C), and relative humidity (75.4 ± 11.97%) were measured, at different times of the year (rainy, transition time and dry periods). From these results a psychrometric chart was constructed and used as a tool for an experimental study focused on the estimation of heat losses in broilers during its finishing period reported elsewhere.